An inverted supramolecular amphiphile and its step-wise self-assembly into vesicular networks. Issue 44 (27th October 2017) - Samanta, Krishnananda; Zellermann, Elio; Zähres, Manfred; Mayer, Christian; Schmuck, Carsten
Abstract : An inverted supramolecular amphiphile self-assembles into 3D networks in a time-dependent process. Abstract : A host–guest interaction between a multi-cationic dendrimer1 functionalized with 16 guanidiniocarbonyl pyrrole (GCP) groups on its surface and naphthalene diimide dicarboxylic acid (NDIDC) in a 1 : 8 ratio leads to the formation of a new type of inverted amphiphile. This amphiphile further self-assembles in a step-wise manner first into reverse micelles and then into reverse vesicles, which adhere to form an extensive 3D network several micrometers in length. Self-assembly is based on the aromatic stacking interactions of the surface-bound NDIDC. Furthermore, these aggregates only form at neutral pH but not in acidic or basic solutions in which no ion pairing between1 and NDIDC is possible. The step-wise self-assembly process of the inverted amphiphile which follows a theoretical prediction recently proposed for hyperbranched polymers was studied and visualized in detail using atomic force microscopy (AFM) and transmission electron microscopy (TEM).